Performance of local exterior masonry against wind-driven rain load - Serra, Jan Victor L.
High wind velocities and precipitation make building envelopes vulnerable to rain infiltration. Various techniques and wall systems are used to prevent rain infiltration. Locally, there are three major types of wall assemblies. These are the single element face-sealed, the multiple element drained cavity and the pressure-equalized rainscreen walls. The study bears two objectives; first (1), to determine the local technologies that addresses rain infiltration and identify the most commonly used technology in the local industry; and second (2), to evaluate the performance of the identified system under various testing configurations. A survey among eight architectural and engineering institutions in Metro Manila revealed that tbe face-sealed wall system is the most common assembly type used in the construction of building envelopes in the Philippines. Then the system was evaluated using ASTM E514 - Standard Test Method for Water Penetration and Leakage through Masonry. For the testing, three configurations with three specimens were fabricated. The first configllration, CHB walls with interior and exterior plaster, exhibited an average infiltration rate of 3.99 L/h. The second configuration, plastered CHB walls coated with latex paint, ex11ibited an average infiltration rate of 0.86 L/h. The third configuration, plastered CHB walls coated with elastomeric paint, exhibited an average infiltration rate of 0.65 L/h. Monk's rating system (1982) has rated the first, second and third configurations as poor, good and excellent respectively. The results showed that the values were significantly different with each other. Among the identified most common local wall configuration, face-sealed walls coated with elastomeric paint is the most effective in preventing water infiltration.